TAM Application Rate Of Application Tracking Interests In Using The Technology Acceptance Model In High Schools In Tangerang District - Ahmad Wiryawan; Widyo Nugroho Nugroho (Dinasti Publisher, 2023)
Interest Searching application is an application to track students' interest in subjects at the high school level in the context of mapping students in high school majors. Websheet-based application from an education consultant, namely CV. Budiwijaya Consultants. This application research was conducted at SMAN Tangerang district as a sample. This study uses the TAM (Technology Acceptance Model) approach model, while the analysis uses Structural Equation Modeling (SEM) analysis with maximum likelihood (ML) estimation, through the AMOS program, of the five variables tested, there is one exogenous variable, namely application features, and four variables. endogenous variables, namely, PU, PEOU, ATU and BITU after being analyzed and adjusting the model as necessary in order to get a good fit model. perceived usefulness (PU), there is also a significant effect on perceived convenience (PU) on user behavior (ATU) as well as on the variable (ATU) against (BITU) having a significant value, while the contribution effect (PEOU) on (PU), and on ( PU) to (ATU) is not significant, from the results of this study it can be concluded that the specialization application has sufficient acceptance. significant up on several variable relationships in the model developed by researchers although it still requires continuous development, so that it is more accepted by users as educational support applications.